The Therapeutic Alliance between Pomegranate and Health Emphasizing on Anticancer Properties - Panagiota D. Pantiora; Alexandros I. Balaouras; Ioanna K. Mina; Christoforos I. Freris; Athanasios C. Pappas; Georgios P. Danezis; Evangelos Zoidis; Constantinos A. Georgiou (MDPI AG, 2023)
Pomegranate is a fruit bearing-plant that is well known for its medicinal properties. Pomegranate is a good source of phenolic acids, tannins, and flavonoids. Pomegranate juice and by-products have attracted the scientific interest due to their potential health benefits. Currently, the medical community has showed great interest in exploiting pomegranate potential as a protective agent against several human diseases including cancer. This is demonstrated by the fact that there are more than 800 reports in the literature reporting pomegranate's anticancer properties. This review is an update on the research outcomes of pomegranate's potential against different types of human diseases, emphasizing on cancer. In addition, perspectives of potential applications of pomegranate, as a natural additive aiming to improve the quality of animal products, are discussed.